Efficiency of six virulence genes detection versus HEp-2 cell adhesion test for diagnosis of enteroaggregative E.coli infection among diarrhea patients - Qiqi CUI; Bing ZHAO; Tongsheng XU; Lipeng HAO; Yingjie ZHENG; Lifeng PAN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectivesTo evaluate the efficiency of detecting six virulence genes of enteroaggregative Escherichia coli (E. coli), abbreviated to EAEC, for diagnosis of EAEC infection among diarrhea patients. MethodsIsolation and identification of E. coli strains were conducted for fecal samples collected from 2 366 diarrhea patients during January 2015 to December 2019 at 12 medical facilities in Pudong New Area of Shanghai municipality. The detection of six virulence genes (aggR, astA, pic, aaiA, aatA, and aaiG) of EAEC and HEp-2 cell adhesion test - the gold standard assay of EAEC were performed on the isolated E. coli strains. The EAEC positivity is determined according to following five positive result combinations of the six virulence genes detection: (1st) both uidA and aggR; (2nd) uidA and any one of aggR/astA/pic; (3rd) uidA and any one of aggR/aatA/aaiG/aaiA; (4th) uidA and any one of aggR/astA/aaiA; and (5th) uidA and any one of aggR/astA/pic/aaiA/aatA/aaiG. Taking the result of HEp-2 cell adhesion test as the gold standard assay, the sensitivity and specificity of the detections of the six virulence genes and their combinations were evaluated using Kappa value, and area under receiver operation curve (AUC). ResultsFor a total of 1 390 E. coli strains isolated from all the samples, 266 (19.14%) were of AA adhesion phenotype and the positivity rate of astA (21.87%, n = 304) was the highest among the six virulence genes detected. According to the standard of HEp-2 cell adhesion test , the detected rate (number) of EAEC positive among the samples from the 2 366 diarrhea patients were 11.24% (266), 2.37% (56), 14.84% (351), 9.68% (229), 5.26% (361) and 16.48% (390/2366) based on the results of the 1st, 2nd, 3rd, 4th, and 5th combination of the six virulence genes detections, respectively, with the highest specificity of 99.86% (2 097/2 100) and the lowest sensitivity of 19.92% (53/266) for the detection of the 1st combination of the six virulence genes. Moderate consistency was observed between the detection results of the standard assay and the 3rd/4th/5th combination of the six virulence genes detection, with the range of Kappa values of 0.58 - 0.65 and the AUC was from 0.806 to 0.882 for the 2nd/3rd/4th/5th combination of the six virulence genes detection, indicating a high efficiency of the detections for the diagnosis of EAEC infection in diarrhea patients. ConclusionThe results of the study suggest that the detection of the six EAEC virulence genes could not substitute HEp-2 cell adhesion test for diagnosing EAEC infection among diarrhea patients.